Effects of Problem-Based Learning Model with Wordwall Media on Students' Critical Thinking Skills - Rana Khairunnisa; Wahyuni Satria Dewi; Yenni Darvina; Dea Stivani Suherman (Jurnal Penelitian Pembelajaran Fisika, 2025)
The research aims to improve the appearance of critical thinking by using a problem-based learning model assisted by wordwall media. Method of research  is quasi-experimental with a post-test only control grup design, the research was done at SMAN 4. The phase E population was sampled using a lateral random cluster, where the control class was phase E7 and the experimental class was phase E6. The assessment is carried out in the form of test questions with cognitive data results as independent variables and skill data as bound variables. The experimental and control classes obtained average cognitive results of 68.61 and 57.22, while the skill scores were 68,5 and 60,56. The magnitude of the relationship between the PBL model with wordwall assistance media and critical thinking skills using a t-test with a calculated t result class experiment of 5.27 and class control is 3.88 with a table t of two class is 2.12. the study concluded that there was a significant relationship and linearity in the PBL model with wordwall assistance media on students' critical thinking skills.